2014
DOI: 10.1007/s10903-014-9992-z
|View full text |Cite
|
Sign up to set email alerts
|

“They Talk Like That, But We Keep Working”: Sexual Harassment and Sexual Assault Experiences Among Mexican Indigenous Farmworker Women in Oregon

Abstract: In order to examine the experiences of sexual harassment and sexual assault among indigenous and non-indigenous Mexican immigrant farmworkers in Oregon's Willamette Valley, a community-academic participatory research partnership initiated a study, which included focus groups, conducted and analyzed by skilled practitioners and researchers. The themes that emerged from the focus groups included direct and indirect effects of sexual harassment and sexual assault on women and risk factors associated with the farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 5 publications
3
23
0
7
Order By: Relevance
“…However, we were surprised to see that the occupational risk factors of years in agricultural work and payment method were associated with AKI in women in our sample. Studies of women's experiences in agricultural work have documented the risk of sexual harassment or assault, which often occurs around bathroom facilities 45 46. Women may tend to limit drinking or eating during their work shift to reduce their need to use these facilities, or may delay trips to the bathroom during the work day out of fear for their safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were surprised to see that the occupational risk factors of years in agricultural work and payment method were associated with AKI in women in our sample. Studies of women's experiences in agricultural work have documented the risk of sexual harassment or assault, which often occurs around bathroom facilities 45 46. Women may tend to limit drinking or eating during their work shift to reduce their need to use these facilities, or may delay trips to the bathroom during the work day out of fear for their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse Mexican Indigenous populations are one of the fastest growing im/migrant communities in the United States. California has the largest population of Indigenous Mexicans in the United States, but Indigenous Mexicans continue to migrate in large numbers to states like Nevada, Oregon, Texas and New York (Murillo and Cerda 2004;Murphy et al 2014;Hester 2015).…”
Section: Situating the Experiences Of Mexican Indigenous Im/migrants mentioning
confidence: 99%
“…Much of the existing literature on Mexican Indigenous im/migrants focuses on the migration of male adults, including their adaptation to and reception from the receiving society (Fox and Rivera-Salgado 2004;Cornelius et al 2007) and adult transnational networks and identities (Kearney 2000;Stephen 2001). More recent work has documented Mexican Indigenous migrant farmworkers' health and experiences of discrimination (Holmes 2013;Murphy et al 2014) as well as health disparities and cultural competency Hester 2015). Relatively little research has focused on the migration experiences of children and families of Mexican Indigenous origin in the United States (Pérez-Rendón 2011; CornejoPortugal and Fortuny Loret de Mola 2012), and even less has focused on their cultural adaptation (Sanchez and Machado-Casas 2009;Casanova 2011) and language socialization (Velasco 2010).…”
Section: Situating the Experiences Of Mexican Indigenous Im/migrants mentioning
confidence: 99%
“…5 A later study of women farmworkers in Oregon also found that WSH was widespread among both Spanish- and indigenous language–speaking farmworkers. 23 However, factors contributing to WSH in this industry and key prevention opportunities remain understudied.…”
Section: Introductionmentioning
confidence: 99%